High-strength optical coatings for single-crystal ZnGeP2 by the IBS method using selenide and oxide materials - Zinoviev, Mikhail M.; Yudin, Nikolay N.; Kuznetsov, Vladimir S.; Podzyvalov, Sergey N.; Kalsin, Andrey; Slyunko, Elena S.; Lysenko, Alexey; Vlasov, Denis V.; Baalbaki, Houssain A. (Ceramics)
The paper presents the results on the development of an optical coating for a single-crystal ZnGeP2 substrate based on a selenide-oxide pair of materials (ZnSe/Al2O3). The obtained coating ensures the operation of OPO in the mid-IR range up to 5 μm wavelengths. The possibility of ZnSe sputtering by the IBS method is shown. The obtained optical coating has a high laser-induced damage threshold (LIDT) value at a 2097 µm wavelength: WEo=3.51 J/cm2 in energy density and WPo = 101 W/cm2 in power density at a 10 KHz pulse repetition frequency and a pulse duration of 35 ns. Thus, it is shown for the first time that the pair of materials ZnSe/Al2O3 can be used for the deposition of optical coatings by the IBS method with high LIDT values for ZnGeP2 optical elements operating in the mid-IR range.